The Role of Wolbachia in DENV Replication as Dengue Control Strategies - Joy Aurel Prudentia Putri; Angelina Vivi Maharani; Condoleezza Betzy Kasi; Loury Priskila; Justinus Agung Putranto Nugroho (Fakultas Kedokteran Universitas Riau, 2026)
Dengue fever (DHF) remains a major public health problem in tropical countries such as Indonesia, with cases continuing to rise in recent years. Conventional vector control strategies are often less effective, creating the need for innovative biotechnology-based approaches. One promising strategy is the utilization of Wolbachia bacteria, which has been shown to suppress dengue virus (DENV) replication in Aedes aegypti mosquitoes. Although its effectiveness is well supported by empirical evidence, the underlying molecular mechanisms remain incompletely understood. Current findings indicate that Wolbachia-mediated inhibition of DENV is multifactorial, involving interactions with the endoplasmic reticulum, competition for cellular nutrients, suppression of pro-viral signaling pathways, regulation of host miRNAs, stimulation of mosquito immune responses, and enhancement of viral RNA degradation. These complex and synergistic mechanisms highlight Wolbachia’s potential not only as a tool for vector control but also as a foundation for developing more effective strategies in dengue prevention and management.